Determinants of financial ratio disclosure patterns of Australian listed extractive companies - Taylor, Grantley; Tower, Greg (Wiley-Blackwell Publishing Asia, 2011)
We investigate the disclosure patterns of Financial Ratios (FRDs) within the annual reports of 111 Australian listed resource companies over the period 2002 to 2006. Disclosure of financial ratio information increased over this period with a significant increase in disclosures recorded in the first full-year annual report prepared following adoption of IFRS. The results of logistic regression analysis demonstrate that income tax and firm size are factors that are significantly associated with financial ratio disclosures. This study contributes to an understanding of the extent, trends and rationale behind resource firms’ financial ratio disclosure practices in Australia.